Electrocardiographic predictors of pacemaker battery depletion: Diagnostic sensitivity, specificity, and clinical risk. Issue 1 (5th December 2019) - Carlson, Daniel; Marine, Joseph E.; Love, Charles J.; Chrispin, Jonathan; Barth, Andreas S.; Rickard, John "Jack"; Spragg, David D.; Berger, Ronald; Calkins, Hugh; Tomaselli, Gordon F.; Sinha, Sunil K.
Abstract: Background: Pacemaker battery depletion triggers alert for replacement notification and results in automatic reprogramming, which has been shown to be associated with relevant cardiorespiratory symptoms and adverse clinical events. Objective: Determine if electrocardiogram (ECG) pacing features may be predictive of pacemaker battery depletion and clinical risk. Methods: This is an ECG substudy of a cohort analysis of 298 subjects referred for pacemaker generator replacement from 2006 to 2017. Electronic medical record review was performed; clinical, ECG, and pacemaker characteristics were abstracted. We applied two ECG prediction rules for pacemaker battery depletion that are relevant to all major pacemaker manufacturers except Boston Scientific and MicroPort: (1) atrial pacing not at a multiple of 10 and (2) nonsynchronous ventricular pacing not at a multiple of 10, to determine diagnostic sensitivity, specificity, and risk in applicable ECG subjects. Results: We excluded 32 subjects not at replacement notification or duplicate surgeries. Overall, 176 of 266 subjects (66.2%) demonstrated atrial pacing or nonsynchronous ventricular pacing on preoperative ECG. When utilizing both rules, 139 of 176 preoperative ECGs and 12 of 163 postoperative ECGs met criteria for battery depletion yielding reasonable sensitivity (79.0%), high specificity (92.6%), and a positive likelihood ratio of 11.6:1. These rules were associated with significant increase in cardiorespiratory symptoms ( P  < .001) and adverse clinical events ( P  < .025). Conclusions: The "Rules of Ten" provided reasonable sensitivity and specificity for detecting replacement notification in pacemaker subjects with an applicable ECG. This ECG tool may help clinicians identify most patients with pacemaker battery depletion at significant clinical risk.